Blaming the young is always more accessible rather than accusing the older employees: an experimental view over age and health in organizations - Man, Gabriela-Maria; Popa, Radu-Ioan; Man, Mihaela (Frontiers in Psychology, 2024)
The stereotype content model postulates that different groups evoke different emotions and reactions based on two dimensions: intention toward others (warmth) and competence. In this study, we used an experimental design and a qualitative approach to investigate how managerial strategies are selected and motivated when a subordinate makes a work task related error but belongs to a group that is stereotypical perceived differently in terms of warmth and competence (age groups with or without a medical condition). Thus 75 employees analyzed one of the five hypothetical cases and described the managerial strategy and motivation for usage. Results revealed that managerial strategies incorporate more active harm elements for younger employees in contrast with vulnerable groups (older employees with unspecified medical conditions, younger or older employees with a medical condition), who benefit from more active facilitation strategies. The strategy usage motivation is also different in the case of younger employees, the control group and the vulnerable groups. The study outcomes bring additional evidence to support the stereotype content model theory and the socioemotional selectivity theory, enriching applicability on organizational practice and human resources management.